Study of far infrared optical properties and, photocatalytic activity of ZnO/ZnS hetero-nanocomposite structure - Zamiri, Reza (2014)
ZnO nanoplates/ZnS nanoparticles as a hetero-nanocomposite structure was prepared by a single pot precipitation method without using any capping ligands or other additives. The morphology of the prepared nanocomposite was studied by scanning electron microscopy (SEM). Optical properties of the prepared samples were studied by UV-visible reflectance and Raman spectroscopy. The FT-IR spectroscopy along with the Kramers-Kronig (k-k) method and classical dispersion theory were utilized to calculate far-infrared optical constants of the prepared samples. The photocatalytic activity of the prepared nanoheterostructure was also assessed in the gas-solid phase, by monitoring the NOx abatement using a white-lamp to re-create an indoor environment.